Consanguinity, complex diseases and congenital disabilities in the Souss population (Southern Morocco): a cross-sectional survey - Noura Dahbi; Abderrazak El khair; Khadija Cheffi; Lamiaa Habibeddine; Jalal Talbi; Abderraouf Hilali; Hicham El ossmani (Egyptian Journal of Medical Human Genetics, 2024)
Abstract Background Several studies showed that the perpetuation of consanguinity increases homozygosity and homogenizes the population's gene pool. This allows the expression of recessive deleterious mutations and increases the prevalence of genetic disorders and birth defects. Despite the reported negative health effects, consanguinity is still practiced in Morocco. This study aimed to evaluate the prevalence and socio-demographic determinants of consanguinity in the Souss region and to assess the association of this type of union with congenital disabilities and complex diseases. To meet this aim, a survey based on a cross-sectional approach was conducted between January 2019 and January 2020 among 520 randomly selected participants in the Souss region. Results The findings revealed a high prevalence of consanguinity of 28.46%, with first-cousin unions accounting for 16.15% of all marriages. According to multivariate logistic regression analysis, early age at first marriage, men’s occupation, endogamy, and parental consanguinity were predictive factors for consanguineous unions in the study population. Moreover, the results revealed a significant association between consanguinity and the incidence of physical disabilities (OR = 3.753; [95% CI 1.398–10.074]), mental retardation (OR = 5.219; [95% CI 1.545–17.631]), deafness-mutism (OR = 4.262; [95% CI 1.004–18.089]) and cardiovascular diseases (OR = 2.167; [95% CI 1.036–4.530]). However, no significant association was found between consanguinity and diabetes, cancer, asthma, epilepsy, and psychiatric disorders. Conclusion Overall, our results suggest a high practice of consanguinity in the Souss population, associated with social, economic, and cultural factors. Consanguineous unions were associated with a high incidence of mental retardation, physical disabilities, deafness-mutism, and cardiovascular diseases. In this population, where marriage between relatives is highly preferred, awareness programs are not sufficient, and genetic studies on consanguinity-related diseases are necessary to provide specific premarital screening and thus increase the efficiency of genetic counseling.